Partisipasi Masyarakat dalam Pelaksanaan Program Keluarga Berencana di Kelurahan Celep, Kecamatan Sidoarjo, Kabupaten Sidoarjo - Nur Aini Rosalia; Deby Febriyan Eprilianto; Muhammad Farid Ma’ruf; Galih Wahyu Pradana (Publika, 2026)
This descriptive qualitative study aims to analyze the low level of community participation in the FamilyPlanning (KB) program in Celep Village, Sidoarjo. This phenomenon is driven by complex factors,ranging from a lack of education and conflicting religious or customary values to inadequate healthfacilities and financial constraints. The research data were gathered through observation, documentation,and in-depth interviews with stakeholders from the Sidoarjo Sub-district, Celep Village officials, andPPKBD/sub-PPKBD cadres. The data analysis followed the stages of data reduction, data display, andconclusion drawing, focusing on four key aspects: community needs, interests, customs, and thecommunal nature of the society. The findings reveal that while the community's need for information hasbeen addressed, the supporting facilities remain insufficient. Community interest is gradually increasingthrough Communication, Information, and Education (KIE) activities, although the use of digital mediafor outreach is still underutilized. Furthermore, there is a dualism in customary and religious perspectives;some residents accept the program for long-term welfare, while others perceive it as opposing divinedestiny. Additionally, while strong communal ties and moral relationships have been established betweencadres and the community, participation remains imbalanced as it is heavily dominated by mothers,whereas the involvement of fathers as key decision-makers remains significantly low.